Pelatihan Pembuatan Website Peminjaman Buku Perpustakaan pada SMA Methodist 4 Medan - Nababan, Labuan; Elnovreny, Jane; Sinambela, Lamtiur; Ginting, Erwin (Yayasan Literasi Sains Indonesia, 2023)
Websites are usually used as a means of conveying or searching for information, for example in the field of borrowing library books. In the development of technology, students are not enough just to be users but must understand more or less how to create websites. Currently, the Medan 4 Methodist school has never implemented practical learning in creating websites, they have only studied Microsoft Office. With the development of technology, schools should have introduced ways of creating websites at the high school level which can later be applied to the school environment and outside the school environment. After holding discussions with the Medan Methodist 4 High School, they needed a complete briefing on the basics of creating a website. This Community Service is a solution to answer the challenges posed by the Medan 4 Methodist High School. This service will provide training to several high school students to become proficient in creating websites. The priority issues include improving skills in website applications, creating students who are skilled in creating website applications. This training can increase students' knowledge regarding creating library websites which can later be improved to create a book lending website at the Medan 4 Methodist School library. This should be overcome with a website-based library information system, because with a website-based information system library data management can be more effective so that the circulation of book loans can be well documented and more effective. With this training, students will be able to contribute a website to the school as their creation.